Community-based accompaniment & social work—A complementary approach to social action. Issue 2 (3rd April 2019) - Wilkinson, Meredith T.; D'Angelo, Karen A.
ABSTRACT: Accompaniment, or the intentional practice of presence, emphasizes processes and relationships over outcomes, with the ultimate goal of leveraging privilege and collectively changing destructive systems. Though not widely recognized in social work, accompaniment has been applied globally. Here, we outline an overview of accompaniment, including how it has been applied in social work literature and practice. We then propose community-based accompaniment as an approach to complement traditional models of social action as a necessary, yet accessible way to further advance community organizing in social work education and practice, and ultimately promote transformative social change.